2016
DOI: 10.3389/fvets.2016.00081
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Masked, and Placebo-Controlled Efficacy Study of Intraarticular Allogeneic Adipose Stem Cells for the Treatment of Osteoarthritis in Dogs

Abstract: Osteoarthritis (OA) is a degenerative joint disease with a high prevalence in dogs. Mesenchymal stem cells (MSCs) have been used to treat humans, dogs, and horses with OA. This report describes a prospective, randomized, blinded, and placebo-controlled clinical efficacy study of intraarticular allogeneic adipose stem cells for the treatment of dogs with OA. Health assessments and measurements of pain and activity impairment were performed at baseline and at selected time points through day 60. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 31 publications
7
98
1
12
Order By: Relevance
“…This approach, mainly based on adipose tissue-derived MSCs, has been demonstrated as clinically safe in several clinical studies in humans (25), dogs (26), and horses (27). A few studies aimed at comparing the safety and efficacy of allogeneic vs autologous MSC in horses, showing controversial results, depending on MSC’s tissue origin.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, mainly based on adipose tissue-derived MSCs, has been demonstrated as clinically safe in several clinical studies in humans (25), dogs (26), and horses (27). A few studies aimed at comparing the safety and efficacy of allogeneic vs autologous MSC in horses, showing controversial results, depending on MSC’s tissue origin.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell research has shown effects in animals. Mesenchymal stem cells have been used in studies in humans for ischemic heart disease, congestive heart failure, wound healing, rejuvenation of aging skin, osteoarthritis, and fracture healing . Outcomes have been mixed.…”
Section: From Stem Cells To Gerotechnologymentioning
confidence: 99%
“…Mesenchymal stem cells have been used in studies in humans for ischemic heart disease, congestive heart failure, wound healing, rejuvenation of aging skin, osteoarthritis, and fracture healing. 49,50 Outcomes have been mixed. Part of the problem is that much of the effect of stem cells is not to engraft into the tissue but rather to create a rejuvenating paracrine milieu with the stem cells and then die off.…”
Section: From Stem Cells To Gerotechnologymentioning
confidence: 99%
“…Sie müssen fähig sein, sich zu Chondrozyten, Adipozyten und Osteozyten zu differenzieren (7,20). Die Darstellung von MSC in der Durchflusszytometrie für die spezifischen positiven und negativen Marker wurde in zahlreichen Studien beschrieben (27,39,43,50,82). Dabei wurden die unterschiedlichen Ausprägungen der Oberflächenmoleküle (z.…”
unclassified
“…Im Rahmen von klinischen Studien steht in der Veterinärmedizin der Einsatz von MSC im orthopädischen Bereich im Vordergrund, wobei hier insbesondere zahlreiche Untersuchungen zur Anwendung von MSC bei Pferd und Hund existieren (18,21,26,31,38,43,46,50,62,65,72,80). Beim Hund kommen MSC zur Bandrekonstruktion (11,46,50) sowie vor allem als alternative oder additive Behandlung bei schmerzhaften (austherapierten) osteoarthrotisch veränderten Gelenken zum Einsatz (8,9,16,26,27,(71)(72)(73). So werden z.…”
unclassified